Gaya Belajar Mahasiswa Pendidikan Sejarah STKIP PGRI Lubuklinggau - Supriyanto Supriyanto; Isbandiyah Isbandiyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The study aims to describe the tendency of students learning style at History Education Study Program of STKIP-PGRI Lubuklinggau. The study was a descriptive study. the subject of the study was the history students in Strategi Belajar Mengajar class. The techniques to collect the data were observation and questionnaire. The data were analyzed descriptively. The results showed that students' learning styles include visual was10,26%, audio was 15,38%, kinesthetic 46% , audiovisual was 5,13%, visual-kinesthetic was 7,69%, audio- kinesthetic was 15,38%. The most preferred leaning style was kinesthetic. Keywords: Learning Styles, Tenden